The effect of serving as a danwei leader before retirement on self-rated post-retirement health: empirical evidence from China - Li He; Kun Wang; Jiangyin Wang; Zixian Zhang; Yuting Wang; Tianyang Li; Yuanyang Wu; Shuo Zhang; Siqing Zhang; Hualei Yang (BMC, 2022)
Abstract Background Worker health is often influenced by their occupation type, and the accumulative effect of occupation has a significant impact on their health after retirement. Studies show that the type and level of occupation before retirement directly impact workers' self-rated post-retirement health. However, there is little research on the self-rated post-retirement health of danwei leaders in China. This study seeks to examine the self-rated health level of Chinese danwei leaders after retirement. Furthermore, the differences between their self-rated health level and that of retirees from other occupations are explored by examining the accumulative effect of occupation and the mechanism underlying these differences. Methods Based on 5,910 samples' data from the 2018 China Longitudinal Aging Social Survey, ordinary least squares, logit, and propensity score matching models are used to investigate the self-rated health level of Chinese danwei leaders after retirement, their differences with other occupations, and the corresponding mechanism. Results The results show that retired danwei leaders have higher self-rated health levels than retirees in other occupations. This was mainly found among female, non-eastern, married, not living with children, and highly educated respondents. The difference in self-rated health between retired danwei leaders and other retired groups was influenced by their post-retirement income and social status. Conclusions In China, retired danwei leaders rated their health higher than retirees from other occupations. Danwei leaders have high socioeconomic status due to their occupation. Compared with other groups, their advantages are significant and enjoyed for a long time. Additionally, most danwei leaders have high social influence even after retirement and their higher income and social status have a positive impact on their self-rated health compared with other employees. This study provides empirical evidence from China and extends current literature on the effects of occupational type and level on self-rated health after retirement.